Circulating interleukin-6 is not altered while γ-tocopherol is increased in subjects scheduled for knee surgery with low vitamin D - Barker, Tyler; Henriksen, Vanessa T.; Rogers, Victoria E.; Momberger, Nathan G.; Rasmussen, G. Lynn; Trawick, Roy H. (Cytokine (Philadelphia, Pa.), 2016)
•Serum IL-6 was not increased by low serum 25-hydroxyvitamin D (25(OH)D).•A decrease in serum 25(OH)D predicted an increase in plasma γ-tocopherol (γT).•An increase in plasma γT was not predicted by a decrease in plasma α-tocopherol. The purpose of this study was to identify if circulating interleukin (IL)-6 and γ-tocopherol (γT) fluctuate with vitamin D status in subjects with an underlying knee joint injury or disease. We hypothesized that low vitamin D associates with an increase in plasma γT while serum IL-6 remains unchanged in subjects with an underlying knee joint trauma or disease. Fifty-four subjects scheduled to undergo primary, unilateral anterior cruciate ligament reconstructive surgery (ACL; n=27) or total knee arthroplasty (TKA; n=27) were studied. Circulating γT, α-tocopherol (αT), lipids (cholesterol and triglycerides), IL-6, and 25-hydroxyvitamin D (25(OH)D) were measured in fasting blood samples obtained prior to surgery. Subjects were classified as vitamin D deficient, insufficient, or sufficient if they had a serum 25(OH)D concentration <50, 50–75, or >75nM, respectively. The majority (57%) of the subjects possessed a serum 25(OH)D less than 50nM. Circulating cholesterol, triglycerides, and IL-6 were not significantly (all p>0.05) different between vitamin D status groups. However, lipid corrected αT was significantly (p<0.05) decreased and both lipid- and non-lipid-corrected plasma γT concentrations were significantly (both p<0.05) increased with low serum 25(OH)D (i.e., <50nM). A significant (p<0.05) multi-variate analysis revealed that an increase in plasma γT per lipids was significantly (p<0.05) predicted by a decrease in serum 25(OH)D but not by a decrease in plasma αT per lipids. We conclude that low vitamin D associates with an increase in plasma γT but not IL-6 in subjects with an underlying joint injury or disease.